A new perspective for sizing of distributed generation and energy storage for smart households under demand response - Erdinc, Ozan; Paterakis, Nikolaos G.; Pappi, Iliana N.; Bakirtzis, Anastasios G.; Catalao, Joao P. S. (ELSEVIER SCI LTD, 2015)
As a recently increasing trend among different applications of smart grid vision, smart households as a new implementation area of demand response (DR) strategies have drawn more attention both in research and in engineering practice. On the other hand, optimum sizing of renewable energy based small scale hybrid systems is also a topic that is widely covered by the existing literature. In this study, the sizing of additional distributed generation (DG) and energy storage systems (ESSs) to be applied in smart households, that due to DR activities have a different daily demand profile compared with normal household profiles, is investigated. To the best knowledge of the authors this is the first attempt in the literature to investigate this issue, also including step-wise decreasing cost functions for DC and ESS, varying load and DG production profiles seasonally, and weekday-weekend horizons for a long-term analysis period. The study is conducted using a mixed-integer linear programming (MILP) framework for home energy management system (HEM) modeling and techno-economical sizing. Also, different sensitivity analyses considering the impacts of variation of economic inputs on the provided model are realized. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Distributed generation; Energy storage; Smart households; Demand response; Home energy management; MANAGEMENT-SYSTEM; OPTIMIZATION; ALGORITHM; IMPACTS; DESIGN; PRICES; PV; Energy & Fuels; Engineering